Osler Centenary Papers: William Osler in medical education. Issue 1130 (21st November 2019) - Leach, Helen; Coleman, Jamie J
Abstract: William Osler combined many excellent characteristics of a clinical educator being a scientific scholar, a motivational speaker and writer and a proficient physician. As we celebrate his life a century on, many of his educational ideals are as pertinent today as they were in those Victorian times. Osler's contributions to modern medicine go beyond his legacy of quotable aphorisms to a doctor, educator and leader whose proponent use of bedside teaching, careful clinical methods, and clinicopathological correlation was a great inspiration for students and junior doctors. He was also a great advocate of patient-centred care—listening to and closely observing his patients, an important message for modern medicine as the reliance on investigations strains modern healthcare systems. This review of Osler's contribution to medical education summarises his development as an educator and provides reflection on his influences to modern clinical education.